Software to facilitate remote sensing data access for disease early warning systems. (December 2015) - Liu, Yi; Hu, Jiameng; Snell-Feikema, Isaiah; VanBemmel, Michael S.; Lamsal, Aashis; Wimberly, Michael C.
Abstract: Satellite remote sensing produces an abundance of environmental data that can be used in the study of human health. To support the development of early warning systems for mosquito-borne diseases, we developed an open-source, client-based software application to enable the Epidemiological Applications of Spatial Technologies (EASTWeb). Two major design decisions were full automation of the discovery, retrieval and processing of remote sensing data from multiple sources, and making the system easily modifiable in response to changes in data availability and user needs. Key innovations that helped to achieve these goals were the implementation of a software framework for data downloading and the design of a scheduler that tracks the complex dependencies among multiple data processing tasks and makes the system resilient to external errors. EASTWeb has been successfully applied to support forecasting of West Nile virus outbreaks in the United States and malaria epidemics in the Ethiopian highlands. Highlights: The EASTWeb software supports early warning systems for mosquito-borne diseases. EASTWeb automates acquisition and processing of remotely-sensed environmental data. Data include temperature, precipitation, spectral indices, and evapotranspiration. These variables are used to develop forecasting models to predict epidemics. EASTWeb has been used to carry out forecasting of West Nile virus and malaria.